2019
DOI: 10.1002/fsn3.973
|View full text |Cite
|
Sign up to set email alerts
|

Content variations in compositions and volatile component in jujube fruits during the blacking process

Abstract: Dried jujube ( Ziziphus jujuba ) was incubated at high temperature and humidity for 96 hr in blacking process and sampled every 12 hr. Results showed that the saccharose reduced from 195.6 to 3.1 g/kg rapidly in 24 hr. The total acid content was mild with 8.82 g/kg and increased to 23.45 g/kg by 177.21% with thermal processing for 96 hr. The contents of total polyphenols were enhanced during 0–48 hr processing, and the amount of the compound increased with treatment by 50.99%. The total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…This result is similar to the results of Y. E. Sun and Wang (2018), which reported that 5‐HMF of garlic treated at 75°C and 75% RH for 12 days rapidly increased, and it was suggested that HMF was generated at high RH and temperature during the Maillard reaction (F. Li et al., 2020; Y. E. Sun & Wang, 2018; X. Sun et al., 2019), although the reason for the quick increase of 5‐HMF is still not clear. Compared with fresh bitter melon, the 5‐HMF content increased by 1.75‐ and 1.54‐fold at 50 and 60°C at day 15, respectively, and there was no significant difference.…”
Section: Resultssupporting
confidence: 90%
“…This result is similar to the results of Y. E. Sun and Wang (2018), which reported that 5‐HMF of garlic treated at 75°C and 75% RH for 12 days rapidly increased, and it was suggested that HMF was generated at high RH and temperature during the Maillard reaction (F. Li et al., 2020; Y. E. Sun & Wang, 2018; X. Sun et al., 2019), although the reason for the quick increase of 5‐HMF is still not clear. Compared with fresh bitter melon, the 5‐HMF content increased by 1.75‐ and 1.54‐fold at 50 and 60°C at day 15, respectively, and there was no significant difference.…”
Section: Resultssupporting
confidence: 90%
“…Analyses of jujube fruits were performed using the HS-GC-IMS instrument as described by Xin et al with slight modifications [31]. Specifically, 1.0 g of fine powder was weighed and placed into a 20 mL headspace-glass sampling vial.…”
Section: Methodsmentioning
confidence: 99%
“…Combining IMS with other instruments is a good way to increase its advantages and produce a good analysis result. In recent years, HS-GC-IMS has been extensively applied to investigate volatile compounds in food science, such as Tricholoma matsutake Singer [22], jujube fruits [31], eggs [26], Iberian ham [32,33], and honey [25]. As a consequence, HS-GC-IMS could be used to identify the volatile components of jujube fruits at different periods.…”
Section: Introductionmentioning
confidence: 99%
“…Combining IMS with other instruments can provide a better effect for characterization of flavor components. Recently, coupling GC column with IMS (GC‐IMS) has been widely applied in the field of food, including wine, eggs, Iberian ham, jujube fruits, and honey . Its effectiveness has been proven to be useful for the analysis and characterization of volatile compounds.…”
Section: Introductionmentioning
confidence: 99%